Estratégias para manutenção do nível de certificação em um hospital Acreditado com Excelência - Elana Maria Ramos Freire (2017)
In a context of promoting continuous improvements and safety of hospital services, Accreditation by the ONA methodology has been outstanding among the methods for evaluating the quality of health organizations. Despite the existence of standards and requirements for the achievement of Accreditation, it is up to each institution to devisestrategies to meet and maintain these requirements. Thus, the objective was to analyze the management strategies to promote continuous improvements in the daily services of a hospital and to maintain the certification of Accredited with Excellence. This is a case study of aqualitative approach carried out in a large private hospital Accredited with Excellence, located in the city of Belo Horizonte, MG. Participated in the research, 22 professionals who work inthe management, coordination and hospital care, as well as professionals directly involved in the Accreditation process. The data were collected through interviews using a semi-structured script, analysis of organizational documents and observation. The analysis of the interviews was done through the technique of "Thematic Content Analysis", using as a theoreticalreference the approach of "strategy as practice". The results were organized into four categories: "The Hospital Accreditation Process: Changes and Challenges", "Strategies for Maintaining Certification of Excellence," "Monitoring and Control of Actions for Quality," and " The strategy in the view of the professionals and their importance for the maintenance of Accreditation". The first category deals with the evolution of the Accreditation process in the hospital, which promoted improvements in communication, physical structure, training and employee involvement, patient and professional safety, among others. As the main challenges, it stands out: professional resistance, obtaining of resources, nursing rotation and change of culture. In the second category, the strategies for maintenance of Accreditation identified were: daily work with quality standards, communication improvements, staff training, internal audits and the strategic role of the Quality Advisor. Among the main actions to monitor the strategies, the following stand out: the use of indicators, half-yearly evaluations for senior management, customer satisfaction, on-site monitoring, internal and external audits. The last category dealt with the understanding of strategy by professionals, which was tied to planning for achievement of results and for implementation of improvements, flexibility and practical implementation of the ideas. There is interdependence and complementarity between the actions and strategies for hospital quality. The importance of communication for employee involvement and participation in the Accreditation process is evidenced, with dissemination of information up to the operational level. Constant training and internal audits have contributed to staff development and process improvement, reflecting quality day-to-day work and certification maintenance.